Keterampilan Berpikir Kritis Siswa dalam Pembelajaran Fisika dengan Model Talking Stick - Abin Hernandi; Resti Warliani; Asep Irvan Irvani (Pendidikan Fisika UIN Alauddin Makassar, 2024)
Critical thinking skills are a thinking skill that is very necessary, one of which is in learning physics. This research explores the importance of critical thinking skills for students and how the Talking Stick model can improve these skills. This research data was obtained from secondary data using the Systematic Literature Review (SLR) research method. The research stages were carried out in accordance with the PRISMA diagram rules, namely identification, screening and included. Through these stages, the final result was 21 articles obtained through the database in the Publish or Perish software. The data obtained was then analyzed using the content analysis method. Based on the results of the analysis, it was found that students' critical thinking skills could improve through the Talking Stick learning model with an average percentage increase of 58.91% with the highest increase being 65,38%. In order to obtain better results of students' critical thinking skills, the support and cooperation of teachers and all related parties is very necessary to play an active role in enriching students' learning experiences in order to improve students' critical thinking skills in physics learning. So it can be concluded that the talking stick learning model can improve students' critical thinking skills.